The impact of COVID-19 on gender inequality in the labor market and gender-role attitudes - Reichelt, Malte; Makovi, Kinga; Sarsgyan, Anahit (European Societies, 2020)
COVID-19 and ensuing changes in mobility have altered employment relations for millions of people across the globe. Emerging evidence shows that women may be more severely affected by this change. The pandemic, however, may have an impact beyond the immediate restructuring of employment and shift gender-role attitudes within households as a result of changes in the division of household labor. We analyze a representative sample of respondents in the U.S., Germany, and Singapore and show that transitions to unemployment, reductions in working hours and transitions to working from home have been more frequent for women than for men – although not to the same extent across the three countries. We also demonstrate that among couples who had been employed at the start of the pandemic, men express more egalitarian gender-role attitudes if they became unemployed but their partners remained employed, while women express more traditional attitudes if they became unemployed and their partners remained employed. These results indicate that gender-role attitudes might adapt to the lived realities. The long-term consequences will depend on how both men and women experience further shifts in their employment relations as economies recove